Are the Mean Platelet Volume and Neutrophil/Lymphocyte Ratio Predictive for Gestational Cholestasis? - Hasan Eroglu; Harun Egemen Tolunay; Kemal Sarsmaz; Gokcen Orgul; Dilek Sahin; Aykan Yucel (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVES: We aimed to determine whether mean platelet volume value and/or neutrophil/lymphocyte ratio values are useful as a predictive marker for gestational cholestasis.